REGULASI DIRI DALAM BELAJAR SISWA SD DIMASA PEMBELAJARAN DARING - Yudhiarti, Ndaru Putri (LPPM STIT Muhammadiyah Tempurejo Ngawi, 2021)
The COVID-19 pandemic has also affected various sectors. In the education sector, face-to-face teaching and learning activities have been stopped with the aim of suppressing the spread of the COVID-19 virus and learning activities are carried out online. Teachers and students are required to be able to make various adjustments to new habits through self-regulation. This study aims to determine the description of self-regulation abilities in student learning at SDN Cepoko 3 during online learning. This study uses descriptive quantitative research methods with the research population of all students of SDN Cepoko 3. The samples in this study were students of grades 4.5, and 6 as many as 53 students. The data collection tool used is a self-regulation scale in learning. With a scale reliability of 0.923. The results showed that the level of self-regulation ability in student learning at SDN Cepoko 3 in Pandemu was in the low category with a percentage of 22.6%, the medium category with a percentage of 45.3%, and the high category with a percentage of 32.1%. This shows that the students of SDN Cepoko 3 in online learning activities during the covid-19 pandemic are able to manage themselves in learning and can make adjustments to the situation.